Amino-acid-based chiral ionic liquids characterization and application in aqueous biphasic systems - Carreira, Ana R. F. (2023)
By using amino acids as anions, ten chiral ionic liquids (CILs) composed of tetrabutylammonium or cholinium as cations were synthesized by neutralization reactions and further characterized by assessing their optical rotation, thermophysical properties (melting and decomposition temperatures, density, viscosity and refractive index) and ecotoxicity against the marine bacterium Aliivibrio fischeri. The CILs are shown to display, in general, high thermal stability (> 439 K) and low to moderate toxicities (86-217 mg·L−1). It was found that the cation plays an important role in the density and viscosity of the CILs. Additionally, the effect of CILs optical configuration on these properties was evaluated by comparing the tetrabutylammonium D/L-phenylalaninate ([N4444][D/L-Phe]) and cholinium D/L-phenylalaninate ([N1112(OH)][D/L-Phe]) pairs. Finally, the CILs potential to form aqueous biphasic systems with sodium sulfate, citrate buffer and phosphate buffer was assessed and the ternary phase diagrams were determined. These allowed to infer the impact of the CILs’ cation, anion, and salt on the aqueous biphasic system formation. It was shown that the cation has a more pronounced impact on the aqueous biphasic system formation than the anion. Cholinium-based CILs failed to form aqueous biphasic systems with sodium sulfate under the tested conditions, contrary to the more hydrophobic tetrabutylammonium-based CILs. The ability of the tested salt and buffers to induce liquid-liquid demixing shows that citrate buffer and sodium sulfate represent the weakest and the strongest salting-out agents, respectively.